Research on the dynamics of Lithuanian state revenue and preferences for expenditure allocation - Skačkauskienė, Ilona (Journal of Business Economics and Management, 2013)
The article analyses revenue and expenditure on the national budget of Lithuania and looks at their dynamics and structure. First, the paper is aimed at naming the main sources of revenue as well as the preferential areas of financing. Second, it is also sought to disclose the objective principles of allocating budget appropriation. To achieve the goal, the correlation between preferences in government activity and expenditure allocation was investigated. The conducted research employs ranging and correlational analysis. Since the formation of a bigger budget leads to an increased appropriation of all functional areas, structural data were analysed thus enabling to more soundly determine whether the distinction of a functional area, as the preferential one, has an influence on its greater significance in the overall system of the national budget. After making the study, no possibility of asserting that a distinction of the preferential functional area is related to its preferential financing exists. In order to summarize the obtained results, it could be claimed that the allocation of resources accumulated by the state would be more substantiated if we related it more with activity priorities of the Government. This would lead to higher objectivity when taking decisions on public administration. First published online: 28 Aug 2013